PENGARUH STRUKTUR MODAL, KEPEMILIKAN INSTITUSIONAL, DAN KEPEMILIKAN MANAJERIAL TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan yang Terdaftar di Jakarta Islamic Index 70 Periode 2021-2024) - Harmayanda Id’ha; Meilda Wiguna; Eka Hariyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2025)
This study examines the effects of capital structure, institutional ownership, and managerial ownership on firm value. The method used in this study is quantitative. The research subjects were companies listed on the Jakarta Islamic Index 70 (JII70) for the 2021-2024 period. The sampling technique used was purposive, with a sample of 38 companies and 152 financial statements. Data analysis used multiple linear regression in SPSS 25. The results show that capital structure affects firm value, while institutional ownership and managerial ownership do not.Keyword: capital structure, firm value, institutional ownership, managerial ownership